EFEKTIVITAS PENDEKATAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN KOLABORASI SISWA - Reswari, Bulqis Banawati; Dzarna, Dzarna; Anggraeni, Astri Widyaruli (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to analyze the effectiveness of the Project Based Learning model in improving students' collaboration skills. PJBL is a learning approach that emphasizes group project work, where students are involved in in-depth exploration of a real problem. This study encourages students to communicate, share tasks fairly and solve problems collectively so that they are able to develop essential collaboration skills in the academic and professional world. Through literature studies and empirical research results, it was found that the PJBL approach contributed significantly to improving students' abilities in dividing tasks fairly, interacting intensively, and sharing responsibilities in a team. Thus, the implementation of PJBL can be an effective strategy in improving students' collaboration skills and creating a more active and meaningful learning environment that is beneficial for future life.